Pengaruh Penguasaan Tata Bahasa & Media Pembelajaran Terhadap Keahlian Menulis Narasi Bahasa Inggris (Eksperimen Smk Swasta Depok): Penelitian - Hana Cintia Ayu Radita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The original objective of this study was to describe the improvement in students’ ability to write English narrative texts by comparing the use of picture series learning media with conventional learning media among 12th-grade students at private vocational high schools in Depok. This study employed an experimental method and is classified as quantitative research. The experimental design used was ANOVA. The research was conducted at two different schools: SMK Asy Syifa as the experimental class and SMK Harapan Bangsa as the control class. The research process lasted for one month, during which the researcher administered exclusive tests to both classes. The results showed that: 1. There was a significant effect of learning media on students’ ability to write English narrative texts, as evidenced by a Sig. value of 0.000 < 0.05 and an F-value of 49.579. 2. There was a significant effect of grammar mastery on students’ ability to write English narrative texts, as evidenced by a Sig. value of 0.000 < 0.05 and an F-value of 46.247. 3. There was a significant interaction effect between learning media and grammar mastery on students’ ability to write English narrative texts, as evidenced by a Sig. value of 0.002 < 0.05 and an F-value of 10.147.